Neuroleptic malignant syndrome cases in a Moroccan intensive care unit: a retrospective analysis and literature review - Soumaya Touzani; Mohammed Hamdouni; Nawfal Houari; Youssef Yaakoubi Khbiza; Abderrahim Elbouazzaoui; Brahim Boukatta; Nabil Kanjaa (Journal of Neurocritical Care, 2021)
Background Neuroleptic malignant syndrome (NMS) is a rare but potentially life-threatening neuropsychiatric emergency. The aim of our study was to update our bedside procedures by investigating NMS cases managed in the intensive care unit (ICU). Methods This retrospective study included all NMS patients admitted to our hospital between January 2012 and December 2019. The variables analyzed included demographics, diagnosis, therapeutics, and outcomes. Results This study included 20 patients, with an average age of 36.6 years. The male to female ratio was 1:4. No patient had a history of NMS, and 60% of the patients had schizophrenia. First-generation neuroleptics (NLs) were the most commonly prescribed drugs (80%). The mean time between the introduction of NLs and onset of symptoms was 7.6 days. Rigidity was observed in 90% of the patients, hyperthermia and neuropsychic syndrome in 65%, and dysautonomia in 50%. The creatine phosphokinase level in all patients was four times the normal value. Mechanical ventilation was required in 20% of the patients and hemodialysis in one patient. None of the patients received specific therapy. The mean duration of ICU stay was 10 days. The mortality rate was 10%,, mainly associated with renal failure. The analysis of the predictors of mortality was limited by the size of our cohort. Conclusion NMS is a rare condition requiring multidisciplinary implementation of contextualized and updated procedures. Early detection and supportive treatment could improve the prognosis in resource-limited settings, where specific treatments are not available. Predictive risk factors should be investigated in larger multicenter cohorts.